Through the Looking Glass: Parental Group Experiences Observing Sensory Motor Therapy - Joan Vertes; Chrystelle Robinson; Veronica Gershenzon; Emily S. Ho; Ashlee Vennettilli (Hindawi-Wiley, 2018)
Objective. The benefits of group therapy in pediatric rehabilitation have been identified. However, a unique small group occupational therapy model with a large emphasis on parental group education and observation of their children has not been extensively studied. In this model, parents observe their child's sensory motor group therapy through a one-way mirror and work with the occupational therapist together after each session, to receive education and develop strategies. In other models, parents sit in the waiting room or observe without working with an occupational therapist as a group afterwards. Method. A descriptive qualitative study was conducted to explore the parental experiences of observing and receiving information as a group regarding their child's participation in sensory motor group therapy. Individual in-depth interviews were conducted with ten parents who observed their children together through a one-way mirror during their children's therapy. Conventional thematic content analysis was used to analyze the interview transcripts to determine themes. Ten parents were interviewed. Results. There were three major themes that surfaced: parent support, the value of observation, and knowledge. Parents enjoyed and perceived benefits for themselves and their children from the opportunity to observe sessions and receive information as a group during therapy. Conclusion. The experiences of parents in this group model suggest that knowledge translation and provision of support to parents and their children regarding their sensory motor needs are beneficial. Administrators may appreciate additional gains of reducing costs and improving access to service.